PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan LQ-45 Yang Terdaftar Di Bursa Efek Indonesia Periode Februari 2010-Januari 2015) - Suroto Suroto (Serat Acitya, 2015)
The aim of this study is to examine effect of investment decisions, financing decisions and dividend policy  on firm value of  companies  in the LQ-45 index  listed on the Indonesia Stock Exchange in the period Februari 2010 to January 2015.  The sample are taken by purposive  sampling. The sample is  16 companies with  sum observation   80. The analysis tehnique in study used multiple regression ordinary least square with α = 0,05. Based on results of data analysis show that Investment decisions significant positive affects on firm value, Financing  decisions  significant  negative affects on firm value and Dividend policy has negative not significant  effect on firm value.  Keyword : firm value, investment decisions, financing decisions, dividend policy.